O frevo e as suas multilinguagens na escola: uma proposta pedagógica para o ensino fundamental II - Santos, Lyane Marcelle Cavalcante (2023)
The main goal of this study was to present a pedagogical proposal based on frevo in a dialogue with other artistic expressions studied in art as well as dance, theater, visual arts, besides to connect with other popular games inserted in a cultural context of students from basic education. It was developed through practice-led research in a classroom of the school "Colégio Municipal Humberto Barradas", located in the municipality of Jaboatão dos Guararapes - Pernambuco state, with students from the 8o anos fundamental. We used the frevo for beyond the civic scholar calendar, creating possibilities to experience it in classrooms during the first semester of 2022. Using multi-languages and multi-facets from the frevo we experience the potential to study this brazilian cultural patrimony in school. As results we present a production of a courseware with exercises that involve the frevo as well creation of a frevo dance group in the school with participation of other teachers in a pedagogical project, promoting a new visibility and recognition of the research with the scholar community.